Good Practices for Gender Responsive Climate Smart Agriculture - Tavenner, Katie; Arora, Diksha; Partey, Samuel Tetteh; Omolo, Nancy; Rao, Nitya; Grist, Natasha; Nguyen Sy Linh (CGIAR GENDER Impact Platform, 2023)
The Compendium of good practices and promising approaches for gender-responsive, climate-smart agriculture is a new collaborative publication between FAO and the CGIAR GENDER Impact Platform, which documents the state-of-the-field on gender-responsive, climate-smart agriculture (CSA) practices, policies, and actions across six regions: Latin American and the Caribbean, East Africa, Southern Africa Development Community, West Africa, South Asia, and Southeast Aisa. Drawing on the Framework for Gender and Socially Inclusive Climate-Resilient Agriculture, the compendium documents good practices and promising approaches across four gender and CSA action areas: (1) field-based evidence on what works for gender equality and women’s empowerment; (2) promoting women’s leadership and decision-making in policy at all levels; (3) closing the gender gap with information, institutions and services; and (4) building mechanisms to engender finance. The good practices and promising approaches to gender responsive CSA compiled in this compendium were gathered from a desk review, analysis of programmatic evidence, and case studies contributed by development practitioners and experts in the different gender action areas. The examples showcased highlight the different gender in/equality dimensions that must be addressed in advancing gender equality and women’s empowerment in CSA: promoting women’s participation in decision-making at household, community, national and global levels; closing gender gaps in access to and use of productive resources and information needed for CSA production; technologies and practices for adaptation and mitigation that reduce workloads and negative impacts on women; and leveraging the power of women’s collective action.